Correction: Effect of network topology and crosslinker reactivity on microgel structure and ordering at liquid–liquid interface. Issue 25 (14th June 2022) - Gumerov, Rustam A.; Rudyak, Vladimir Yu.; Gavrilov, Alexey A.; Chertovich, Alexander V.; Potemkin, Igor I.
Abstract : Correction for 'Effect of network topology and crosslinker reactivity on microgel structure and ordering at liquid–liquid interface' by Rustam A. Gumerov et al., Soft Matter, 2022, 18, 3738–3747, ; https://doi.org/10.1039/D2SM00269H .